Effects of Institutional Quality on FDI in Provinces of Vietnam: Empirical Evidence Based on Differenced Panel GMM - Nguyen, Van Bon (University of Economics Ho Chi Minh City, 2023)
Foreign direct investment (FDI) has been strongly affecting the world economy during the past years and is a critical topic for both developing and developed countries. Most countries, particularly developing ones, always attempt to adjust and modify appropriate policies and institutions to attract FDI inflows. In the context of Vietnam, does the institutional quality have any effect on attracting FDI inflows in provinces? To answer clearly and exactly this question, the impact of institutional quality on attracting FDI inflows is empirically investigated in a sample of 43 provinces of Vietnam over the period of 2005–2012 via the estimation technique of difference panel GMM. Estimated results indicate that in the total sample of all provinces the institutional quality has significantly positive effects on the FDI flows. However, in the sub-sample of provinces the impact of the institutional quality on attracting FDI inflows in Northern and Southern regions are statistically significant while that in Central region is not.